FAKTOR YANG MENYEBABKAN MASYARAKAT TIDAK MENGGUNAKAN HAK PILIHNYA DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR TAHUN 2013 DI TPS 5 RT 4 RW 1 KELURAHAN TUAH KARYA KECAMATAN TAMPAN - Putra, Rona Desmara; Marnelly, T. Romi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Lately, most of the people of the city of Pekanbaru many who opted for abstention or abstain from voting in the democratic party of the people, due to the weakened and low antusiasi society to the General Election. In addition to the above problems finding the low level of community participation has also become a serious problem that occurs in each of the Sub-District of the election of the Governor and Deputy Governor of the city of Pekanbaru years 2013. Because of that conducted a study entitled "Factors That Cause Public Not to Use Rights Vote In Elections Governor and Deputy Governor in 2013 in TPS 5 RT 4 RW 1 Tuah Karya’s Village Tampan’s Subdistrict".The purpose of this study is: 1) To determine the characteristics of the respondents chose to abstain from voting on the election of governor and lieutenant governor in 2013 on the TPS 5 RT 4 RW 1 Tuah Karya’s Village Tampan’s Subdistrict. 2) To determine the cause of the people chose to abstain from voting on the election of governor and lieutenant governor in 2013 on the TPS 5 RT 4 RW 1 Tuah Karya’s Village Tampan’s Subdistrict. To determine the factors that cause people chose to abstain from voting on the election of governor and lieutenantgovernor in 2013 on the TPS 5 RT 4 RW 1 Tuah Karya’s Village Tampan’s Subdistrict. 3) To determine the relationship of socio-economic background of the respondents who chose to abstain from voting on the election of governor and lieutenant governor in 2013 on the TPS 5 RT 4 RW 1 Tuah Karya’s Village Tampan’s Subdistrict.The benefits of this research are: 1) It is expected that these results obtained contribute ideas for the development of the science of sociology. 2) As an input and information for other researchers in further research, so that it can add a reference to the study of science as well as other existing beneficial to the development of the academic world in the future.The procedure of this study can be seen from the following steps: the issues examined in this study is what factors are causing the people in the polling station 5 RT.4 RW.1 jl. Organization, Work Tuah Village, District of Kampar. The method used in the study is the method of questionnaires, interviews, and use documents. Research tool used was a questionnaire that was developed with the interview. From the research results and conclusions: 1) Characteristics of voters who abstain from voting at the polling station 5 RT 4 RW 1 Tuah Karya’s Village Tampan’s Subdistrict of respondents aged between 33-38 years who do not choose more than any other age (24%). 2) Most of the voters who did not choose to work as traders and students respectively of 6 people (24%). 3) The level of education they are mostly located at the upper secondary level (high school) as many as 12 respondents (48%). 4) Respondents who do not use their right to vote mostly Muslim, as many as 22 people (88%). 5) The majority of voters who abstain from voting are from ethnic Minang many as 10 people (40%). 6) Most of the voters settled in research sites in jl. swadaya, already including long over 6-15 years as many as 12 people (48%). 7) Respondents who do not use their right to vote most have incomes tend to be low, ie below Rp.1.500.000, - which is the minimum wage of Riau province.Keyword : Politic, Participation, Pilgubri 2013